Studying Artificial Intelligence and Artificial Sociality in Natural Sciences, Engineering, and Social Sciences: Possibility and Reality - Dr.V.H.Prasad,K Naresh Kumar,M Shailaja (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The authors will briefly describe how some of today’s innovations and advancements might provide potential for improving the efficiency, effectiveness, and quality of contem- porary teaching methods. A model curriculum proposed in this paper merges the disciplines of mathematics, science, engineering, and computing. It also addresses the growing need for exposing aspiring engineers to the human, cultural, and professional aspects of their emerging careers.